2006
DOI: 10.1084/jem.20060894
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the defective interaction between a subset of natural killer cells and dendritic cells in HIV-1 infection

Abstract: In this study, we demonstrate that the in vitro interactions between a CD56neg/CD16pos (CD56neg) subset of natural killer (NK) cells and autologous dendritic cells (DCs) from HIV-1–infected viremic but not aviremic individuals are markedly impaired and likely interfere with the development of an effective immune response. Among the defective interactions are abnormalities in the process of reciprocal NK–DC activation and maturation as well as a defect in the NK cell–mediated editing or elimination of immature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
167
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(175 citation statements)
references
References 53 publications
7
167
0
1
Order By: Relevance
“…The perturbations observed in the NK cell compartment during chronic HIV-1 infection include the overall increased activation of NK cells, the early loss of CD3 Ϫ CD56 bright NK cells, the accumulation of anergic CD3 Ϫ CD56 Ϫ CD16 ϩ NK cells (6,10), and the impairment of their cytotoxic capacity (6,9,10,56) and cross-talk with DCs (11). The mechanisms underlying these numeric and functional NK cell perturbations observed during viremic HIV-1 infection are not understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perturbations observed in the NK cell compartment during chronic HIV-1 infection include the overall increased activation of NK cells, the early loss of CD3 Ϫ CD56 bright NK cells, the accumulation of anergic CD3 Ϫ CD56 Ϫ CD16 ϩ NK cells (6,10), and the impairment of their cytotoxic capacity (6,9,10,56) and cross-talk with DCs (11). The mechanisms underlying these numeric and functional NK cell perturbations observed during viremic HIV-1 infection are not understood.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells are furthermore capable of secreting a number of cytokines and chemokines early in viral infections that are critical in the initiation of an effective adaptive immune response (5). It has been reported that significant changes occur within the NK cell compartment during HIV-1 infection (6 -9), including perturbations in the distribution and function of NK cells, accumulation of anergic NK cells (6,10), and an impairment of NK-dendritic cell (DC) 3 cross-talk (11). Furthermore, NK cells are activated in HIV-1-infected individuals more than in matched seronegative controls (12).…”
mentioning
confidence: 99%
“…However, a study by Alter et al has shown that even though viremic HIV-1 infection is associated with a reduction in NK cell numbers and a perturbation of NK cell subsets, the overall NK cell activity is increased (46). In addition, a recent report has shown that in HIV-1-infected viremic patients a subset of NK cells lacking the expression of CD56 (CD56 Ϫ NK cells) has an altered expression of NKp30, a NCR, which leads to highly defective NK cell-mediated lysis of autologous dendritic cells (47).…”
mentioning
confidence: 99%
“…In line with these data, NK cells from acute myeloid leukemia (AML) and HIV patients, which frequently express an NKp30 dull phenotype 63,64 had an impaired ability of killing DCs. 65,66 Moreover killing of DCs can also be inhibited in the presence of TGF-b, a cytokine inducing a profound downregulation of the surface expression of NKp30. 67 On the other hand tryptophan, catabolite L-kynurenine (IDO), although affecting NK cell-mediated killing of tumor cells by downregulating the expression of NKp46 and NKG2D, does not impair NK-mediated DC killing because it has no effect on NKp30 expression.…”
mentioning
confidence: 99%